ANALISIS PEMBELAJARAN DALAM MENGEMBANGKAN KREATIVITAS ANAK USIA 5-6 TAHUN DI TK BINA 45 PONTIANAK - Aprianti, Rika; Ali, Muhamad; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this research was to describe the lesson of teacher?s developing the crativity of children aged 5-6 years at the Bina 45 Kindergarten Pontianak. The method use is this research is descriptive method with a qualitative research approach. Data subjects in this research are 2 teacher?s and 15 childern of group B2 with age 5-6 years in Bina 45 Kindergarten Pontianak. The techniques used in this research were observation, interview, and documentation using data collection tools like is observation guidelines, interview guides, and documentation picture. The results of data analysis show that : (1) The planning of learning by the teacher includes the preparation of determining themes, indicators, learning outcomes, and organizing learning materials, tools and resources, (2) The implementation of learning by teacher includes opening activities, activities core, and closing activities. (3) Evaluation of learning by the teacher includes observation, anecdotal recording, conversation, assignment, and appearance.Recommended for teacher?s becomes better and more fun, to be more creative in developing skills from various media learning.Keyword : Childern 5-6 Years Old, Creativity Development, Learning